SIGNIFIKANSI ASBÃB AN-NUZÃL DALAM PENAFSIRAN ALQURâAN - Karim, Abdullah (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
The study of asbÃ¢b an-nuzÃ»l is a part of the Qurâanic studies that discussed about events or questions directed to Rasulullah Saw. so then Quraâanic verses was gone down as the answer or the explanation of them. Based on the definition, it is not included reports or events that happened in the past before, such as Abrahahâs arrival with his troops is not asbÃ¢b an-nuzÃ»l for Sura al-FÃ®l, so do the stories of Noahâs clan, âAdâs, TsamÃ»dâs, etc. This article discusses about two matters. First, what are asbÃ¢b an-nuzÃ»l exactly? And second, what is the significance of it to understand the meaning of Qurâanic verses? After all, there are some conclusions. AsbÃ¢b an-nuzÃ»l talked about the reality in Qurâanic verses when they are gone down and shahÃ®h reports must accommodate them. AsbÃ¢b an-nuzÃ»l is very important to understand the meaning of Qurâanic verses for some reason. They will help Qurâanic reader to know the secret behind the appearance of a verse or more, to know the limit of a rule for certain verses, etc.